“Multiple Cardiac Rhabdomyomas in a Newborn Successfully Treated with a TOR inhibitor: A Case Report” - Hammoud MD, Mohamad; Saad, George; El Bachour, Joseph (Journal of Neonatal Surgery, 2025)
Introduction:Cardiac rhabdomyomas are the most common primary cardiac tumors in neonates and are strongly associated with tuberous sclerosis complex (TSC). While most lesions regress spontaneously, extensive or multifocal tumors may lead to ventricular dysfunction, arrhythmias, or hemodynamic compromise, prompting consideration of targeted therapy with mammalian target of rapamycin (mTOR) inhibitors. Case Report:We report a male neonate born at 36 weeks’ gestation with prenatally detected intracardiac masses. Postnatal echocardiography revealed multiple large cardiac rhabdomyomas diffusely involving all cardiac chambers, causing marked reduction in ventricular cavity size, biventricular diastolic dysfunction, and moderate pericardial effusion, with preserved outflow tracts. Brain magnetic resonance imaging demonstrated multiple subependymal tubers, confirming the diagnosis of TSC. Everolimus therapy was initiated early in the neonatal period. After three doses, a significant reduction in tumor size and improvement in ventricular function were observed. The infant developed frequent ventricular arrhythmias, which were successfully controlled with low-dose sotalol. Follow-up echocardiography at one month showed marked further regression of the rhabdomyomas and sustained clinical stability. Discussion:This case illustrates the role of cardiac rhabdomyomas as an early diagnostic marker of TSC and supports the effectiveness of mTOR inhibition in achieving rapid tumor regression in neonates with extensive cardiac involvement. However, the persistence of arrhythmias despite significant tumor reduction suggests that electrical abnormalities may not parallel structural improvement, highlighting the need for continued rhythm surveillance and adjunctive antiarrhythmic therapy. Conclusion:Early recognition of TSC-associated cardiac rhabdomyomas and prompt initiation of Everolimus can result in rapid tumor regression and functional improvement, potentially avoiding surgical intervention. Comprehensive multidisciplinary follow-up remains essential to address ongoing cardiac and neurological risks and to better define the long-term safety of mTOR inhibitors in neonates.